Optimization of Criteria for Manual Smear Review Following Automated Blood Cell Analysis - رسلان, ديمه; تغريد قدّار (Latakia University Journal -Medical Sciences Series, 2022)
Introduction:The complete blood count (CBC) with differential leukocyte count is one of the most requested blood tests in medical laboratories. The CBC test is used to assess general health and to detect a wide range of disorders, including anemia and leukemia, and it measures the three blood cells: red blood cells (RBC, HCT, HB, erythrocytes indices), white blood cells (number and differential counts), and platelets. Despite the high accuracyand scalability of automated blood analyzers, review of manual smears is still necessary to identify some morphological abnormalities that may be relatively unnoticeable with automated methods. Automatic counts use Flags alert messages directing the necessity of conducting a blood smear examination for some samples. The international consensus group suggested that each laboratory adopt its own standards for blood smear review, but many laboratories use factory settings, which is the case in our laboratory. Each laboratory should have its own criteria that reduce the workload and limit the conduct of smears without affecting patient care, as manual smear review is labor-intensive, time-consuming and may not be necessary. This research aims to compare international consensus group standards with our laboratory standards to improve it, to obtain better performance efficiency and to develop a systematic method that combines statistical analysis and clinical judgment to improve signal thresholds on automated counters. Methods: The study sample includes patients attending Tishreen University Hospital in Lattakia. A venous blood sample was drawn on EDTA K3 tube, then CBC test was performed on Medonic M20 Basic device in the central laboratory at Tishreen University Hospital.A blood smearwas performedfor each sample with flag. Results: Compared with that of our laboratory criteria and factory settings criteria, the efficiency of the consensus group criteria was higher (41.47% versus 40.20 %, 39.24%, P < 0.05) respectively, the review rate was lower (38.65 % versus 50.92 %, 54.97 %, P < 0.05) respectively, and the false-positive rate was lower (18.55 % versus 28.32 %, 32.06%, P < 0.05) respectively. After optimizing the rules, we obtained an efficiency of 41.87 %, a review rateof49.81%, and a false-positive rate of 22.91%. Conclusion: All laboratories should have itsown criteria for smear review. Criteria can be based on the consensus group criteria but should be verified before adoption or optimized to be suitable for different requirements.